2014
DOI: 10.1371/journal.pcbi.1003447
|View full text |Cite
|
Sign up to set email alerts
|

A Division in PIN-Mediated Auxin Patterning during Organ Initiation in Grasses

Abstract: The hormone auxin plays a crucial role in plant morphogenesis. In the shoot apical meristem, the PIN-FORMED1 (PIN1) efflux carrier concentrates auxin into local maxima in the epidermis, which position incipient leaf or floral primordia. From these maxima, PIN1 transports auxin into internal tissues along emergent paths that pattern leaf and stem vasculature. In Arabidopsis thaliana, these functions are attributed to a single PIN1 protein. Using phylogenetic and gene synteny analysis we identified an angiosperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
203
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(214 citation statements)
references
References 57 publications
10
203
1
Order By: Relevance
“…The auxin pathway is also regulated by KNOX proteins (Bolduc et al, 2012). Auxin triggers initiation of lateral primordia and accumulates distally in developing leaves (Reinhardt et al, 2003;O'Connor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The auxin pathway is also regulated by KNOX proteins (Bolduc et al, 2012). Auxin triggers initiation of lateral primordia and accumulates distally in developing leaves (Reinhardt et al, 2003;O'Connor et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in light of the fact that similar developmental impairments have been shown in some monocots [113][114][115][116][117] and that homologs of PIN genes have been identified in gymnosperms [118,119], it is generally thought that the auxin mechanism of phyllotaxis regulation may be universal throughout the seed plants. Sequencing analyses have suggested that PIN genes may be present in the seedless land plants as well [119], and PAT has been shown to be present in Physcomitrella [120] and Selaginella [121], indicating that the auxin mechanism of phyllotaxis formation may be common to all land-plant lineages.…”
Section: Regulation Of the Phyllotactic Pattern Formation -Similaritimentioning
confidence: 96%
“…Distinct regulators of PIN1 localization were shown to be involved in these different phases -whereas the localization towards the convergence point is regulated in part by the serine/threonine kinase PINOID (Friml et al, 2004), which phosphorylates PIN1 (Huang et al, 2010), the switch to basal polarization is regulated by the MAB4 gene family (Cheng et al, 2008;Furutani et al, 2014). In angiosperm species other than the Brassicaceae, leaf initiation and vascular formation were suggested to be regulated by distinct members of the PIN family (O'Connor et al, 2014).…”
Section: The Role Of Auxin During Leaf Initiationmentioning
confidence: 99%